A rare case of multidrug resistant Leclercia adecarboxylata catheter-related bloodstream infection and an updated brief literature review - Cosimo Colangelo; Giorgio Tiecco; Marco Di Gregorio; Susanna Capone; Roberto Luigi Allegri; Maria De Francesco; Francesca Caccuri; Arnaldo Caruso; Francesco Castelli; Emanuele Focà (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Leclercia adecarboxylata is a gram-negative bacillus, a ubiquitous microorganism, which may be found in both aquatic environments and soil, it was first described by H. Leclerc in 1962 and was reclassified thanks to more sensitive testing methods. L. adecarboxylata has been recently recognized as an emerging pathogen that causes several clinical syndromes not only in immunocompromised patients.